The advantages of fentanyl for the treatment of pain: Studies of pharmacological profiles and fentanyl relatedside effects - Arief Nurrochmad; Ozaki Masahiko; Minoru Narita; Tsutomu Suzuki (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
The understanding of the pharmacological profiles of fentanyl and fentanyl-related side effects seems to be critical for the management for control of pain. Therefore, the present study was designed to investigate the advantages for treatment with fentanyl and the side effects such as emesis and gastrointestinal transit inhibition. The results demonstrated that fentanyl produced a profound antinociception in ferrets and mice than that induced by morphine. These findings are consistent with the experiences in the clinic. Morphine with lower doses than antinociceptive doses, produced a significant increase in gastrointestinal transit inhibition. However, fentanyl produced no gastrointestinal transit inhibition unlike morphine. These findings are consistent with the clinical experiences in the use of fentanyl. The clinical studies in patients chronic cancer pain showed that transdermal therapeutic delivery system for fentanyl (TTS-fentanyl) produces less side effects such as constipation, nausea and vomiting than that induced by oral morphine. Morphine with lower doses than that used for antinociceptive assay also produced either in the number of retching or vomiting. However, fentanyl failed to produce emetic response in ferrets. These findings indicate that fentanyl produces much less emesis than that induced by morphine. Finally, we conclude that fentanyl produced potent antinociception in ferrets and mice. In addition, fentanyl produced much less side effects including emesis and constipation. These findings may provide evidence for benefit and usefulness of fentanyl for clinical frame on the management of pain treatment.Key word: fentanyl; antinociception; emesis; ferret.